Semi-presidentialism, moderating power and inclusive governance. The experience of Timor-Leste in consolidating democracy - Feijó, Rui Graça (2012)
The relationship between the choice of a government system, namely semi-presidentialism, and the performance of democracy is the subject of current debate. This article considers Elgie's proposal for a positive correlation between premier-presidential forms of semi-presidentialism and the success of democratic transitions, and discusses the way in which Timor-Leste fits the model as well as the need for a clear view of the incentive mechanisms at play. It further analyses the importance of “independent” presidents with “moderating powers” as a way of achieving inclusive governance and to facilitate democratic consolidation. Contrary to suppositions that attribute a tendency for president-parliamentary regimes to succumb to conflict between the main political actors, the case of Timor-Leste suggests that the definition of the president's role as a “moderator”, and the exercise of the function by “independent”, non-party personalities counteracts such inclinations with positive effects on democratic consolidation.